Chemoselective synthesis and evaluation of β-oxovinylarsines as an arsenic synthetic precursor - Tay, Wee Shan (2022)
β-Oxovinylarsines are introduced as a stable and highly functionalized bench-top arsenic precursor. Stereoselective syntheses furnished geometrically pure cis- A nd trans-isomers from the same ynone under different conditions. The organic Michael acceptor backbone allowed β-oxovinylarsines to be easily applied to conjugate-addition reactions, and β-oxovinylarsines were reactive to nucleophiles, electrophiles, and transition metals. Unlike other arsenic precursors which are toxic or volatile or have low reactivity, β-oxovinylarsines bear a well-defined organic backbone that confers both stability and known reactivity. Remarkably, β-oxovinylarsines were also compatible with organometallic catalysts and did not decompose or deactivate the catalyst by chelation.